Access to human tissues for research and product development. (7th April 2015) - Pirnay, Jean‐Paul; Baudoux, Etienne; Cornu, Olivier; Delforge, Alain; Delloye, Christian; Guns, Johan; Heinen, Ernst; Van den Abbeel, Etienne; Vanderkelen, Alain; Van Geyt, Caroline; van Riet, Ivan; Verbeken, Gilbert; et al.
<x xml:space="preserve">Abstract</x> Private biotech companies are increasingly seeking to research and create products that use human cells and tissues from public biobanks. Greater discussion is needed about the serious legal and ethical issues surrounding the use of donated biological material to generate profit.